She wants you - Billie; Marr, Jim; Page, Wendy; Virgin Records (London : Virgin Records, 1998)
Contains three tracks from the album'Honey To The B'.
CD 1 : She Wants You (album version) / (3:38) -- Last Christmas / (4:59) -- She Wants You (sharp'ballroom' remix) / (8:27).
Koleksi Khas Wiramanja.
Keywords: Songs, English